Evaluasi Sistem City Dashboard Menggunakan Framework ITIL Versi 3 - Alayya Nurin Sani; Rita Wahyuni Arifin; Harjunadi Wicaksono; Sigit Setiawan (Ikatan Ahli Informatika Indonesia, 2024)
The City Dashboard system is an important tool to fulfill the information needs in the context of smart cities, focusing on six main principles including connectivity, security, energy efficiency, mobility, governance, and environmental sustainability. With the increasing complexity and volume of data that needs to be managed by local governments, the presence of a City Dashboard is becoming increasingly crucial in supporting fast and precise decision-making. However, the City Dashboard System faces several problems that need to be fixed immediately. First, the City Dashboard System is not consistent in presenting data according to the specified time frame to users. In addition, there is no feedback mechanism from users, which hampers the process of improving and developing the dashboard. Finally, there are often page display problems that are under repair, hampering the optimal performance of the system. Immediate improvement efforts are needed to present data consistently, obtain user feedback, and ensure optimal availability of the City Dashboard System. This study aims to conduct an in-depth evaluation of the effectiveness of the City Dashboard system using the ITIL Version 3 framework with the Service Operation domain which focuses on 3 Service Operation sub-domains, namely Event Management, Request Fulfilment, and Incident Management. The evaluation results of the Bekasi City Dashboard System show a maturity level at level 4 (Managed and Measurable) with an average score of 3.50, which means that the maturity level of the City Dashboard System has been implemented as a whole at each layer involved (managers and users) and has been well managed.